2010
DOI: 10.1002/anie.201004340
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopic and Theoretical Analysis of a Spontaneously Formed Lys–Asp Isopeptide Bond

Abstract: One bond makes all the difference: Three suitably positioned amino acid side chains (see picture) and a hydrophobic environment are all that is required for an amidation reaction with remarkable consequences. An emerging central building block of bacterial surface proteins owes its stability to a spontaneously formed isopeptide bond. The impact of this bond on protein structure and dynamics and the mechanism of its formation are scrutinized in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 25 publications
3
111
0
Order By: Relevance
“…The latter also polarizes the C = O bond of the Asn or Asp side chain, resulting in a partial positive charge on Cγ (10,14). This is essentially a one-turnover autocatalytic reaction dependent on the polarity of the environment and the proximity of the reacting groups.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The latter also polarizes the C = O bond of the Asn or Asp side chain, resulting in a partial positive charge on Cγ (10,14). This is essentially a one-turnover autocatalytic reaction dependent on the polarity of the environment and the proximity of the reacting groups.…”
Section: Significancementioning
confidence: 99%
“…It includes not only Gram-positive pili but a number of other cell surface adhesins, known as microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) (7). Examples of the latter include the collagen-binding A domain and repetitive B domains from the Staphylococcus aureus collagen-binding surface protein Cna (8,9), the fibronectin-binding protein FbaB from S. pyogenes (10), and the adhesin SspB from Streptococcus gordonii (11). In contrast to the Gram-positive pili, which are assembled from discrete protein subunits (pilins) by sortase enzymes (12), the MSCRAMMs are typically single polypeptides folded into many domains.…”
mentioning
confidence: 99%
“…These intramolecular isopeptide bonds have now been characterized experimentally in a wide-range of pilus subunits from many Gram-positive pathogens (reviewed in refs. 7-9) and also in the MSCRAMM FbaB (10). Intramolecular isopeptide bonds are most commonly formed between the side chains of Lys and Asn residues ( Fig.…”
mentioning
confidence: 97%
“…Intramolecular isopeptide bonds are most commonly formed between the side chains of Lys and Asn residues ( Fig. 1) [although Lys-Asp bonds also exist (10,11)]. The residues comprising these bonds are strategically positioned to bridge the first and either penultimate or last β-strand of the Ig-like domains.…”
mentioning
confidence: 99%
“…Within CnaB2, there is a spontaneous reaction to form an isopeptide bond between Lys and Asp, catalyzed by an apposed Glu (Fig. 1A) (13,14). We previously showed that the CnaB2 domain could be split into two parts to enable protein-peptide ligation, via isopeptide bond formation between a peptide tag (i.e., SpyTag) and a protein domain (i.e., SpyCatcher) (15).…”
mentioning
confidence: 99%